Desain Hotel Resort Bintang 3 Di Puumbara Desa Rate Rua Kecamatan Ende Utara Kabupaten Ende - Mbuu, Alfons; Ora, Adrianus Paulus (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2021)
Hotel is a type of accommodation that uses part or all of the building that provides lodging, food and beverage services and other services for the public, which are managed commercially. Providing recreational and entertainment facilities, sports and fitness facilities, business and office service facilities, financial service facilities, shopping facilities, as well as the development of other supporting facilities needed for guest and visitor activities. The method used is an architectural design method with the concept of Post Modern Architecture as a design reference. The analysis used in this design includes environmental analysis, actor analysis, spatial scale analysis, shape analysis and outdoor space analysis. The results obtained from the design of the 3-star Puumbara resort hotel in Raterua Village are presenting nature-related tourism in hilly areas with the concept of a post-modern architectural theme. The application of the theme in the design is the difference in ground elevation and the use of hard materials such as wood, paving blocks, garden lights, and soft materials such as grass and shade vegetation and ground cover.